Osteoblast Proliferation is Enhanced upon the Insulin Receptor Substrate 1 Overexpression via PI3K Signaling Leading to Down-regulation of NFκB and BAX Pathway - Ma, H.; Ma, JX.; Xue, P.; Gao, Y.; Li, YK. (Experimental and Clinical Endocrinology & Diabetes, 2015)
The insulin receptor substrate 1 (IRS1) promotes bone formation via osteoblast proliferation mediated by PI3K/Akt signaling. A reduction in NFκB activity in osteoblasts results in an increase in bone formation. The NFκB signaling pathway leads to increased expression of BAX, which contributes to osteoblast apoptosis. The purpose of this study was to investigate the expression of recombinant plasmid enhanced green fluorescent protein-N1 (pEGFP-N1) that transferred IRS1 gene into osteoblasts in vitro and evaluate the effects of IRS1 overexpression on NFκBp65 and on BAX. Osteoblasts were transfected with pEGFP-N1 or pEGFP-N1 encoding wild-type IRS1 (pEGFP-N1-IRS1). Cell cycle analysis was performed using flow cytometry. The expression levels of NFκBp65 and BAX were measured by Western blotting. Our results revealed that overexpression of IRS1 stimulated osteoblast proliferation, as evidenced by an increase in the number of cells in the S phase compared to controls. IRS1 overexpression in osteoblasts activated the PI3K/Akt pathway, and inhibited expression of NFκBp65 and BAX. When osteoblasts transfected with pEGFP-N1-IRS1 were exposed to a PI3K inhibitor (LY294002), the effects of IRS1 overexpression were reversed. On the basis of our study, it seems that osteoblasts proliferated upon IRS1 overexpression due to inhibition of the NFκB pathway and downregulation of BAX through PI3K/Akt signaling.
Keywords: insulin receptor substrate 1; PI3K signaling; osteoblast proliferation; NFκBp65; BAX